1996
DOI: 10.1016/s0969-2126(96)00153-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure of UDP-N-acetylglucosamine enolpyruvyl transferase, an enzyme essential for the synthesis of bacterial peptidoglycan, complexed with substrate UDP-N-acetylglucosamine and the drug fosfomycin

Abstract: The present structure reveals the mode of binding of the natural substrate UDP-GlcNAc and of the drug fosfomycin, and provides information on the residues involved in catalysis. These results should aid the design of inhibitors which would interfere with enzyme-catalyzed reactions in the early stage of the bacterial cell wall biosynthesis. Furthermore, the crystal structure of MurA provides a model for predicting active-site residues in EPSP synthase that may be involved in catalysis and substrate binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
281
1
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(291 citation statements)
references
References 37 publications
6
281
1
3
Order By: Relevance
“…Specifically, fosfomycin binds to and inhibits the cytoplasmic enzyme uridine diphosphate N-acetylglucosamine (UDP-GlcNAc) enolpyruvyl transferase (MurA). This enzyme is responsible for the synthesis of UDP-Nacetylenolpyruvylglucosamine, which is a metabolic pentapeptide intermediate in the biosynthesis of the peptidoglycan layer of the bacterial cell wall [37]. To exert its action, fosfomycin needs to penetrate the bacterial cell membrane.…”
Section: Pharmacodynamic Characteristics Of Fosfomycinmentioning
confidence: 99%
“…Specifically, fosfomycin binds to and inhibits the cytoplasmic enzyme uridine diphosphate N-acetylglucosamine (UDP-GlcNAc) enolpyruvyl transferase (MurA). This enzyme is responsible for the synthesis of UDP-Nacetylenolpyruvylglucosamine, which is a metabolic pentapeptide intermediate in the biosynthesis of the peptidoglycan layer of the bacterial cell wall [37]. To exert its action, fosfomycin needs to penetrate the bacterial cell membrane.…”
Section: Pharmacodynamic Characteristics Of Fosfomycinmentioning
confidence: 99%
“…13 The metal is pentacoordinated in a trigonal-bipyramidal fashion, with the glutamate oxygen and the oxirane oxygen in the axial positions. EPR studies of FosA showed that the Mn 2+ ion (3d 5 ) is in the high-spin sextet state. 21,22 Interestingly, a K + ion was found in a loop close to the active site, consistent with the important role of K + for enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the discovery that Cys-115 could be replaced by an aspartate without loss of activity (a mutation found in some bacteria including Mycobacteria) led to the conclusion that Cys-115 functions as a general acid-base catalyst and not as a nucleophile in the reaction with PEP (10). Cys-115 is a member of a 10-residue loop in the N-terminal globular domain that undergoes drastic conformational changes upon binding of UNAG by approaching the interdomain cleft and positioning the Cys-115 side chain into the PEP binding site (11)(12)(13)(14)(15). Cys-115 has received considerable attention as the target of covalent modification by fosfomycin (12) and other electrophilic natural products such as terreic acid (16) and cnicin (17).…”
mentioning
confidence: 99%